2007
DOI: 10.3347/kjp.2007.45.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA virus in Korean Isolate IH-2 of Trichomonas vaginalis

Abstract: Abstract:In this study, we describe Korean isolates of Trichomonas vaginalis infected with double-stranded (ds) RNA virus (TVV). One T. vaginalis isolate infected with TVV IH-2 evidenced weak pathogenicity in the mouse assay coupled with the persistent presence of a dsRNA, thereby indicating a hypovirulence effect of dsRNA in T. vaginalis. Cloning and sequence analysis results revealed that the genomic dsRNA of TVV IH-2 was 4,647 bp in length and evidenced a sequence identity of 80% with the previously-describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Our study found that 90% of the fresh isolates were infected with TVVs, confirming the high prevalence observed in previously study that found dsRNA particles in 82% of T. vaginalis isolates in South Africa (Weber et al, 2003). A study conducted in Korea found that only 13.6% of the isolates were infected with TVVs, showing that the infection rate may vary according to geographical location (Kim et al, 2007). Regarding the prevalence of TVVs species, TVV1 was found to be the most prevalent, followed by TVV2, TVV3, and TVV4.…”
supporting
confidence: 94%
“…Our study found that 90% of the fresh isolates were infected with TVVs, confirming the high prevalence observed in previously study that found dsRNA particles in 82% of T. vaginalis isolates in South Africa (Weber et al, 2003). A study conducted in Korea found that only 13.6% of the isolates were infected with TVVs, showing that the infection rate may vary according to geographical location (Kim et al, 2007). Regarding the prevalence of TVVs species, TVV1 was found to be the most prevalent, followed by TVV2, TVV3, and TVV4.…”
supporting
confidence: 94%
“…Large variability is found in the prevalence values, from 13 to 90% of T. vaginalis isolates harboring TVVs 134139140. The participation of the virus in the virulence of T. vaginalis is under investigation.…”
Section: Pathogenicity - Opening the "Black Box" Of Trichomonas Vaginmentioning
confidence: 99%
“…To screen T. vaginalis isolates for trichomonasviruses, dsRNA extracts from cultured T. vaginalis cells were used to carry out RT-PCR using the Qiagen one-step RT-PCR kit with species-selective screening primers (see Table S1 in the supplemental material), designed from previously reported TVV sequences (5,6,25,40,41,51). The presence of an ϳ500-bp band, which when sequenced showed homology to a known trichomonasvirus sequence, was taken as confirmation for the presence of that species in the T. vaginalis isolate.…”
Section: Ethicsmentioning
confidence: 99%
“…For full-length sequencing of cDNA strands for trichomonasviruses from T. vaginalis isolates UR1 and UH9, various internal fragments of each viral genome were amplified by reverse transcription followed by PCR, using other forward and reverse primers designed from the previously reported TVV sequences (5,6,25,40,41,51). The sequences from both strands of each amplified fragment were then determined in full directly from the PCR products.…”
Section: Ethicsmentioning
confidence: 99%
See 1 more Smart Citation